APPLYING THE LEARNING MODEL STUDY CRUSH THE RIGHT TO INCREASE ACTIVITY AND ACHIEVEMENT STUDENTS CLASS IV STATE Klepu 02 SD TP SEMESTER II 2015/2016 - Samain, Samain (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2017)
The main problems faced in learning PKn is the low level of student involvement at a time when learning is taking place, especially to the study of the arrangement of the Central Government, the students looked enthusiastic to follow the lessons. The matter then raises the low learning achievement of students. The effort to enhance the learning of students in leraning PKn activities, particularly material about the arrangement of the Central Government, one of which can done by applying the model 3T. Class action research model Kemmis McTaggart was used in this research. Data collected through two techniques: observation and tests. The validity of the data specified with triangular. The analysis technique used is descriptive qualitative. Full length research with three cycle namely throuhg cycles of 1,2 and 3, with a very significant results as follows: first cycle of activities by students on average; 50.00%, test scores with a mean: 63.57%, cycle II students activities on average; 82.00%, with test scores average: 72.14%, cycle III the students activities with an average; 86.00%, with tes scores average: 83.50%. With the results of the study showed that by applying the learning model 3T and student learning outcomes activities increased.